PENGARUH VARIASI LARUTAN ELEKTROLIT TERHADAP PRODUKSI BROWN’S GAS - Ena Marlina (INFO-TEKNIK, 2016)
The need of energy is increasing continuously and the reliance of fossil fuels is very great, looking at condition te be sure is needed a certain research which focuses to find the altenative. By conduction in hopefully the solution will be found. By separation of H2O (Water) to be Hydrogen (H2) dan Oxygen (O2) using electrolysis chemical reation, this research uses KOH and NaHCO3 catalist with the percentage of each 0; 1; 2; 3; 4 % as a trigger to compare each other in order to accelerate the H2O electrolysis process. It also uses SS 306 L electrode with tho chathode and anode number which are Wet cel. Overdel, the result in every research the percentage of KOH solution has high value because it is a good conductor and the biggets Brown’g gas which is produted is 16,33 ml/s with 231 Watt electric consumtion while if uses NaHCO3 the  Brown’g gas 12,675 ml/s with 283,08 Watt electric consumtion.